Invasion of exotic piscivores causes losses of functional diversity and functionally unique species in Japanese lakes. (18th May 2016) - Matsuzaki, Shin‐ichiro S.; Sasaki, Takehiro; Akasaka, Munemitsu
Summary: Human activities affect not only species richness (SR) but also functional diversity (FD), but the consequences of species loss on FD may vary among communities. The loss of functionally unique species can result in a greater loss of FD, undermining the long‐term persistence of ecosystems. We quantified the temporal changes in the SR and FD of native fish communities at the lake and drainage basin scales ( N  = 45), and investigated the relationships among these declines in SR and FD, anthropogenic drivers, and lake morphometric characteristics. We also simulated random species loss and compared the observed FD to the expected FD to examine whether losses of functionally unique species from the lakes and drainage basins had occurred. Overall, SR and FD at the lake scale decreased by 72.1 and 75.5% from historical to current (since 2000) time periods, respectively, but the loss rates were mitigated at the drainage basin scale because some of the species that have disappeared from lakes persist in the surrounding waterbodies. Of the drivers we considered, the richness of exotic piscivores was the most important predictor of changes in both SR and FD. Increases in exotic piscivore richness reduced the SR and FD. The consequences of species loss on FD varied among the lakes. Loss of functionally unique species at the lake scale occurred in 18 lakes and tended to be associated with increased exotic piscivore richness. In 5 of the 18 lakes, however, functionally unique species persist in the surrounding waterbodies. The persistence of these species may have the potential to increase the FD of lake fish communities. Our findings suggest the importance of the strategic management of exotic piscivores and interconnections between lakes and their surrounding waterbodies to ensure the persistence of native fish assemblages and associated ecological functionality.